PENERAPAN MODEL COOPERATIVE SCRIPT BERBANTUAN MEDIA ALAT PERAGA TARBOL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS DI SD 1 JATI WETAN KUDUS - Puspitasari, Puteri (Journal Prakarsa Paedagogia, 2024)
AÂ This research aims to describe (1) the application of the Cooperative Script learning model assisted by tarbol media in increasing the learning activity of class V students in science and soscial subjects at SD 1 Jati Wetan Kudus (2) the application of the Cooperative Script learning model assisted by tarbol media in improving teacher skills in science and soscial subjects for class V at SD 1 Jati Wetan Kudus, (3) the effect of implementing the Cooperative Script learning model assisted by tarbol media on increasing the classical learning completeness of class V students in science Â and soscial subjects at SD 1 Jati Wetan Kudus. The conclusion of this research is that the application of the Cooperative Script model assisted by Tarbol media can increase the learning activity of class V students in science and soscial subjects at SD 1 Jati Wetan.Â